ASPEK PENYELENGGARAAN HUKUM PRAKTIK KEDOKTERAN BERDASARKAN UNDANG-UNDANG NO. 9/2004 TENTANG PRAKTIK KEDOKTERAN - Redyanto Sidi (Jurnal Penelitian Kesmasy, 2022)
The community is not just an object but also as a subject of health services, therefor, the implementation of public health services is the responsibility of government and community. A strategic public policy such as Medical Practice Act No. 29 of 2004, is expected to overcome problems related to health services. Two basic issues of this regulation, firstly, to protect community from an exploitative and unethical of medical practice which may decrease community trust toward medical professions; secondly, to provide a legal certainty and legal protection of medical profession against an excessive community litigation